2022
DOI: 10.1007/s13668-022-00414-3
|View full text |Cite
|
Sign up to set email alerts
|

Digital Marketing of Breast-Milk Substitutes: a Systematic Scoping Review

Abstract: Purpose of Review Globally, too few children are breastfed as recommended. Commercial promotion of breast-milk substitutes (BMS) is one factor undermining breastfeeding globally. Although the International Code of Marketing of BMS prohibits all forms of marketing, promotion has been observed in digital environments. We aimed to understand the scope and impact of digital marketing for the promotion of BMS. Recent Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 22 publications
1
20
0
9
Order By: Relevance
“…This review also reported an increase in marketing through digital platforms and brand extensions. Digital marketing of BMS is not only common, but particularly challenging to measure [26]. As with all digital marketing, messages about specific products can be tailored to individual consumers through multiple globally used platforms.…”
Section: Chilementioning
confidence: 99%
“…This review also reported an increase in marketing through digital platforms and brand extensions. Digital marketing of BMS is not only common, but particularly challenging to measure [26]. As with all digital marketing, messages about specific products can be tailored to individual consumers through multiple globally used platforms.…”
Section: Chilementioning
confidence: 99%
“…By contrast, the most common violation of the Thai Act was BMS marketing to mothers, and IF product marketing was the most common violation of the Act. Recently, a review of the scope and impact of digital marketing of BMS has proposed new national and international initiatives to address this type of marketing (47) . This issue is being reviewed by WHO, to develop new guidance on restricting digital marketing (48) .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The urgent call for a monitoring system for BMS and FBHFSS marketing on digital environments is given by the marketing techniques’ ability to increase consumer demand and consumption, with the corresponding risk for adequate feeding practices (e.g., breastfeeding or intake of healthy foods and beverages) [ 72 , 73 ], health consequences, and economic loss [ 74 , 75 , 76 ]. This marketing influence on purchasing decisions has also been described for tobacco and alcohol [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies ( n = 13) focused on monitoring the marketing of FBHFSS targeted toward adolescents. The latter finding is of relevance, considering the influence of BMS marketing on infant feeding practices and the number of WHO Member States that have not yet adopted legal measures to implement at least some of the Code’s provisions [ 73 ]. Of the 144 member states, 28.5% (41 countries) are moderately aligned with the Code, and 22.2% (32 countries) are substantially aligned [ 11 ].…”
Section: Discussionmentioning
confidence: 99%